Caracterización de pacientes con retinopatía diabética en Bogotá D.C 2019 (2020)
Diabetic retinopathy (DR) is a microangiopathy that affects the retinal vasculature, considered the most common microvascular complication of diabetes mellitus (DM) type I and II, located within the first causes of low vision and/or blindness in the world. Literature describes changes related to the time of evolution of the condition are reported, such as microaneurysms, retinal hemorrhages, hard exudates and soft, venous beading, intra-retinal microvascular anomalies, macular edema and neovascularization. This document presents the analysis of the socio-demographic characterization and anthropometric conditions of 15 patients diagnosed with DM.